Problems in inverse scattering of approximate reflection coefficient measurements - Kincanon, Eric (International Journal of Applied Mathematical Research, 2016)
Because of the nonlinear nature of the Gelfand-Levitan equation, it may be a concern that a small difference in the reflection coefficient could lead to large changes in the corresponding potential. This paper considers this and shows that this need not be a concern. Though assumptions are made about the associated spectral measure function, these are not restrictive.